The philosophy of Michel Henry (1922-2002) a French Christian phenomenology of life - Rebidoux, Michelle (Lewiston : Edwin Mellen Press, 2012)
This text traces a genealogy of phenomenology by bringing attention to Michel Henry in lieu of this ongoing philosophical discourse. His views on life are seen as answering questions opened up by other widely known philosophers such as Kant, Descartes, Nietzsche, Heidegger, and Plato, among others. This book seeks to explore the importance of a 20th Century French philosopher whose views on life are equally as important as the aforementioned thinkers because it addresses their unanswered questions. The author also offers her own original critiques of Henry's work as well.
Introduction -- Chapter 1: (En)countering Heidegger. 1.1. Heidegger's critique: being and beingness ; 1.2. Descartes' beginning: videre vs. videor ; 1.3. Heidegger's hesitation: Ereignis and Ab-grund ; 1.4. A counter-tradition: life and the unconscious -- Chapter 2. Phenomenology and givenness. 2.1. Husserl's 'principle of principles': givenness ; 2.2. Givenness as 'first philosophy': Jean-Luc Marion's 'saturated phenomenality' ; 2.3. The transcendental ego: ideal essence vs. ipseity -- Chapter 3. Material phenomenology. 3.1. Subjectivity and objectivity: the three bodies ; 3.2. Given life: the 'double revelation' ; 3.3. The problem of forgetfulness: 'impropriation' -- Chapter 4. Henry's Christianity. 4.1 The influence of neo-Platonism: Henry's Eckhart ; 4.2. A phenomenology of Christ: onto-theology and the problem of solipsism ; 4.3. The problem of language: the word essence ; 4.4. Henry's ethics: 'disimpropriation' and action ; 5. Community, time and 'the call' ; 5.1. Alpha omega: life's 'multiple-self-community' ; 5.2. The problem of the infinite: the flesh and the icon ; 5.3. Marion's critique: the 'pure call' -- Conclusion.
Includes bibliographical references (p. 245-260) and index.
Description based upon print version of record.
Keywords: Henry, Michel, -- 1922-2002.; Phenomenology; Christian philosophy; Christian philosophy; Henry, Michel, 1922-2002.; Phenomenology; Philosophy; PHILOSOPHY / History & Surveys / Modern; Electronic books